Sistem Informasi Absen Karyawan Menggunakan QR Code Berbasis Mobile Pada Kantor Korwil Sanga Desa - Yulisa Toyyiba; Rahayu Amalia (Teknik Komputer Politeknik Negeri Sriwijaya, 2023)
This research is entitled employee absence information system using a mobile-basedQR Code at the Sanga Desa Korwil office. One of the main components in the world of work isattendance or attendance list. With this presence, work in a company can run in a structuredand orderly manner. Along with high mobility, the use of smartphones is now also used tosupport work activities, one of which is to do attendance. However, not many companies areusing this technology in their companies. This study aims to build a mobile-based employeeattendance system using a QR Code. This application allows users to fill in attendance easily,so employees who have limited time and do not have time to fill out the attendance list form caneasily fill out the attendance list.